Nutrition studies in Peru - Guzmán Barrón, Alberto (1956)
In this paper a summary of research conducted by the Institute of Biochemistry and Nutrition, Faculty of Medicine of Lima regarding nutritional problems Peru is made. To this end there have been clinical, haematological and biochemical studies to identify deficiency states in groups of individuals from different economic classes, soldiers, adults, children and seniors. Regarding calorie needs an applicable table shows the average weight in relation to age, obtained from national surveys. Protein deficiencies, the solution would be in the highest consumption of fish are detected. Referring to the lack of calcium in the diets is shown that by the constant action of the solar rays properly manage groups examined using the poor contribution. Alkaline phosphatase determinations reveal absence of rickets. A high percentage of anemia in the jungle due to high intestinal parasitism and overall diets contain adequate proportion of iron is, low hemoglobin in the other groups would be due to inadequate intake of other substances involved in the synthesis of hemoglobin. Lower values are ascorbic acid, according to the amounts of the vitamin deficient in the diet in almost all the groups. Studies in relation to vitamin B complex deficiency show that reaches almost all groups examined and proposed as an immediate solution fortification of flour or rice with thiamine, riboflavin and niacin. Measuring the sedimentation rate as a resource for the recognition of states of undernutrition is proposed because there are parallels between physiological poverty and accelerated speed.